Engines of the mind : - Shurkin, Joel (Norton, 1984)
Engines of the Mind. The Evolution of the Computer from Mainframes to Microprocessors. Joel N. Shurkin (Author). Sign up for the ... Here is the first full account of an invention that changed the world.